Analisis Disiplin Kerja dalam Meningkatkan Produktivitas Kerja Karyawan Cipta Grafika Karawang - Anggi Noviandra Rahmadanty; Suroso; Flora Patricia Anggela (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and analyze the implementation of work discipline in increasing employee work productivity at Cipta Graphic Graha Karawang. The research approach used is qualitative with a descriptive method, which aims to explain the characteristics of the variables that are the focus in analyzing work discipline and employee work productivity at the Cipta Graphic printing press in Karawang. Data collection methods include interviews, observation and documentation studies, with data validity strengthened through triangulation of data sources. The results of the analysis show that work discipline at Cipta Graphic Graha Karawang tends to be good, although there are still several cases of employees arriving late. The main causes include late arrival to work and non-compliance with SOP (Standard Operating Procedures). Efforts to overcome this problem are carried out through the application of sanctions in accordance with regulations and collective agreements, as well as evaluation through recording Error Logs and weekly evaluation meetings to correct work errors that are not in accordance with the SOP (Standard Operating Procedures).